Heavy metals loads in soil, farmlands and plant crop at open dumpsite - O.B. Akintan; J.A. Olusola; A.M. Azeez (Global Journal of Environmental Science and Management)
This study aimed to evaluate concentrations of selected heavy metals in the soils of Ilokun dumpsite and adjourning farmlands, and to determine as well levels of heavy metals uptake in various parts of Carica papaya plant collected from the dumpsite. Twenty-two soil samples were collected within the dumpsites and farmlands at depths of 0-20 cm and 20-40 cm. Evaluations of heavy metals (Ni, Zn, Cd, Cr, Pb and Cu) in soil samples and in different parts of Carica papaya plants were carried out using atomic absorption spectrophotometer. The study revealed higher concentration of Pb in the dumpsite than the farmlands. Mean concentrations of Cd in the dumpsites; 2.98±1.93 (0-20 cm) and 3.22±2.14 (20-40 cm) were higher than their corresponding depth in farmlands (1.93±1.28 (0-20cm) and 1.94±1.59 (20 – 40 cm). The study established a strong correlation for Ni/Pb (0.948) at depth of 0.20cm; Cu/Cd (0.985) and Pb/Cd (0.918) at depth of 20-40cm. Heavy metal uptake was highest in the plant parts compared to the dumpsites and farmlands. The result showed that translocation factor arrangement is: Cu ˃ Zn ˃ Cd˃ Cr˃ Pb˃ Ni and Cu had the highest translocation factor of 4.698. Based on the results, the various heavy metal could be classified as slight contaminants (Pb, Cr and Ni), moderate contaminants (Cu and Cd) and severe contaminant (Zn). Although concentrations of heavy metals in the farmlands were below the Department of Petroleum Resources and World Health Organisation allowable limits, monitoring the concentration profile of these heavy metals concentrations in the area is recommended to prevent detrimental effects on the environment.